Apakah Pengalaman Wisata yang Berkesan mempengaruhi Niat Berkunjung Kembali Wisatawan Domestic ke Atraksi Wisata Tanah Lot? A CASE STUDY AT TANAH LOT TOURIST ATTRACTION, TABANAN REGENCY - Wiryaguna, I Gede Patria; Susianti, Woro; Widana, Ida Bagus Gede Agung (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
Memorable Tourism Experience (MTE) refers to a significant experience that tourists remember and build upon when describing a specific visit to a travel destination. This experience can be used to gauge the level of interest and its impact on the likelihood of revisiting the destination. This study aims to investigate the effect of MTE on the revisit intention of domestic tourists to Tanah Lot Tourist Attraction in Tabanan Regency. The research employs a quantitative approach, using both primary and secondary data sources. Data from 350 respondents were collected via a questionnaire and subsequently analyzed using multiple linear regression techniques with SPSS version 25 for Windows. The findings indicate that the dimensions of hedonism, local culture, refreshment, involvement, meaningfulness, and knowledge have a positive and significant effect on the revisit intention of domestic tourists to Tanah Lot Tourist Attraction. Conversely, the dimension of novelty has a positive but not significant effect. The simultaneous test shows that MTE has a positive and significant effect on the revisit intention of domestic tourists to Tanah Lot Tourist Attraction. The determination test results reveal an R² value of 0.636, indicating that Memorable Tourism Experience accounts for 63.6% of the variance in revisit intention among tourists at Tanah Lot Tourist Attraction. The remaining 36.4% is influenced by other variables not examined in this study.